Relentless Mining in Meghalaya, India - Sarma, Kiranrmay; Yadav, Pramod K (Conservation Science, 2013)
Local people of Meghalaya and migrants from neighboring states and even from Bangladesh have started mining to survive, putting increased pressure on land and water supplies. The mining activities have brought in the desired effect of economic growth but on the other hand, affected the environment in a variety of ways, which contributed to its degradation. The pertinent question that everybody needs to ask: who pays the cost of degradation? Local indigenous people who are not knowledgeable about future disaster are not able to bear the cost. Scientists must speak loudly about the impending disaster of natural resources exploitation to make this knowledge available to others in a form that can impact decision making. DOI: http://dx.doi.org/10.3126/cs.v1i1.8578 Conservation Science 2013 1(1), 5-12